A basic study for the molecular imaging of dual-energy CT in diagnosing anterior cruciate ligament injury of knee joint. (April 2023) - Bai, Rui; He, Xiaohua; Huang, Juncheng
Background: Anterior cruciate ligament (ACL) injury is a common disease in clinical practice that seriously affects the daily life of patients. Purpose: To explore the molecular imaging basis of "diminution sign on dual-energy colour mapping" for the diagnosis of ACL injury by dual-energy computed tomography (DECT). Material and Methods: The hydroxylysine and hydroxyproline reagents were prepared in different concentrations. The grouping was shown as follows: a simple concentration change group of an amino acid (group 1/2); a mixed solution group with the concentration increasing synchronously (group 3); a mixed solution group with the concentration reverse increasing and decreasing (group 4); and a mixed solution group that fix one amino acid with increasing concentration of the other (group 5/6). The samples were scanned by DECT. The solution CT value and image signal-to-noise ratio were analyzed. Results: In group 1/2, the brightness of the dual-energy color mapping of each test tube solution and the CT value increased with increasing the concentration of amino acid. In group 6, there was no significant change in the brightness and brilliance of the dual-energy color mapping and the CT value. The remaining three groups showed an increase in the brightness and brilliance of the dual-energy color mapping and the CT value, and this increase was positively associated with the hydroxylysine concentration. Conclusion: The dual-energy staining of the DECT imaging in "tendon" mode is related to hydroxylysine and hydroxyproline. Moreover, the degree of dual-energy color mapping is positively correlated with the change of CT value.